216 Can we mitigate castration pain in beef cattle? -What it means for animal comfort, productivity and consumer perception. - Schwartzkopf-Genswein, K (J Anim Sci, 2018)
It is well documented that castration, regardless of age or method (surgical or band) causes pain in beef cattle. At the same time, consumer concern and awareness regarding painful routine management procedures in livestock is at an all-time high. Developing pain mitigation strategies that are practical and cost effective for producers is also important to facilitate their adoption by the beef industry. The goal of this talk is to review current pain mitigation strategies for both knife and band castrated calves as well as their effectiveness in controlling calf pain and improving calf comfort. The link between the development and adoption of these strategies for castration (or any other painful procedure) and consumer perception and approval of Canadian beef products will also be discussed. Pain mitigation strategies to be covered will consist of both non-therapeutic and therapeutic methods. A discussion of non-therapeutic methods will include the effects of calf age and method of castration. Therapeutic methods to be discussed will consider the effects of different types and combinations of drugs, timing of drug administration, and pain control for multiple procedures. Finally, the relationship between pain mitigation strategies and calf growth performance will be examined. Continued research assessing new drugs or modes of administration as well as alternative methods is required to ensure the availability of practical and effective on-farm methods of mitigating both procedural and postoperative pain. Focus on such strategies will aid in improving cattle welfare and industry adoption of best management practices as well as consumer confidence in beef products, ultimately contributing to the sustainability of the Canadian beef industry.